Households of the Roman urban élite in Aquincum – Villa of the White Storks (Folyamőr street 14-16, Budapest, Hungary). Imported and Local Pottery - Magyar-Hárshegyi, Piroska; Gabler, Dénes (Rei Cretariae Romanae Fautorum Acta, 2022)
A decorated Roman luxurious building complex with mosaics and frescoes was excavated opposite the Governor’s palace, in the canabae legionis of Aquincum, in the modern Folyamőr street (Budapest). The aim was to analyse the finds of these nearly 40 years old excavations and draw a more complex picture on the every-day life of the Roman provincial high class in Aquincum. In this paper we would like to publish the most important features of samian ware, amphorae, ‘rätische Wareʼ, ‘Pannonische Glanztonwareʼ, lamps and coarse ware were in use in the three distinctive period of this site, from the last third of the 1st to the middle of the 3rd century AD.